Efeito do tipo de dieta e do sistema de alimentação na fase inicial sobre o desempenho de leitões - Berto, D. A.; Kronka, R. N.; Thomaz, Maria Cristina [UNESP]; Kronka, S. D. (Revista Sociedade Brasileira Zootecnia, 1997)
In this experiment, 96 piglets (Large White x Landrace) were fed simple (SD) or semi-complex (SCD) diets during the initial phase (SP), using a controlled (C) or ad libitum (AL) schedules during the first 14 days of the SP and ad libitum for the rest of SP. By the end of SP one male and one female from each pen were transferred to growing finishing pens where they were fed ad libitum diets specific to each phase. The experimental design consisted of randomized complete blocks with six replicates by treatment. Higher average daily feed intakes (ADFI) were observed during the first 14 days of the SP by pigs fed SCD. Pigs fed AL showed higher ADFI and average daily gains (ADG). No treatment differences were observed between the treatments in feed conversion (FC) or in incidence and severity of diarrhea. Considering SP as a whole, there was no effect of treatments on the variables studied. Treatments used in SF did not affect ADFI and ADG during the growing-finishing phases (GFP), although pigs fed SD showed better FC. The ADG was nor affected by treatments when the total period (SP+GFP) was considered. It can be concluded that a similar performance was obtained when SD or SCD were feci during the initial phase. independently of the feeding system.
Effect of the type of diet and feeding system at initial phase on the performance of piglets
Keywords: performance; diarrhea; growing-finishing phase; weaning pigs; Feeding system; diet type